The future development of the the audio and electronic books in the Republic of Kazakhstan (Herald of Journalism, 2020)
The aim of the article is the analysis of the future development of   the the audio and electronic books in the Republic of Kazakhstan, main directions and prospects of development publishing and book market in Kazakhstan.
Keywords: audio, electronic book, publishing house, book trade, book publishing.